1966
DOI: 10.1079/bjn19660022
|View full text |Cite
|
Sign up to set email alerts
|

Rumen development in the calf

Abstract: I . Twenty-four Ayrshire bull calves were reared on either high-concentrate or high-roughage diets to study the effect of diet on the subsequent ability of the calf to digest either concentrates or hay when given alone. The rearing diets were known to produce different types of rumen development. 2. Although there were significant differences between the apparent digestibility coefficients of the high-concentrate and high-roughage rearing diets and between concentrates and hay when given alone, the subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

1970
1970
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 36 publications
1
20
0
2
Order By: Relevance
“…A mixture of SCFA salts (propionate and butyrate included) fed as 10% (wt/wt) of a concentrate starter ration resulted in increased incidence of ruminal parakeratosis, and in all treated animals a thickening of the stratum corneum was reported in calves (Gilliland et al, 1962) and lambs (Rickard and Ternouth, 1965). Increasing amounts of concentrate in the diet resulted in no change in rumen muscularity but did result in increased papillae density and papillae height in calves (Stobo et al, 1966) and lambs (Rickard and Ternouth, 1965). None of these studies were able to definitively distinguish the mechanism responsible for the induction of papillary development.…”
Section: Development Of the Ruminal Epitheliummentioning
confidence: 95%
“…A mixture of SCFA salts (propionate and butyrate included) fed as 10% (wt/wt) of a concentrate starter ration resulted in increased incidence of ruminal parakeratosis, and in all treated animals a thickening of the stratum corneum was reported in calves (Gilliland et al, 1962) and lambs (Rickard and Ternouth, 1965). Increasing amounts of concentrate in the diet resulted in no change in rumen muscularity but did result in increased papillae density and papillae height in calves (Stobo et al, 1966) and lambs (Rickard and Ternouth, 1965). None of these studies were able to definitively distinguish the mechanism responsible for the induction of papillary development.…”
Section: Development Of the Ruminal Epitheliummentioning
confidence: 95%
“…These authors reported that as the concentrate intake increased, the hay intake decreased linearly [5,36], while live and empty body weight (BW) and rumen development were improved [36]. This is probably because concentrates result in more VFA production, especially propionate and butyrate [12], which enhances papillae development [13,36]. Collectively, these early studies suggested that in a high roughage feeding system, the addition of a bulky forage in the diet might decrease the consumption of energy-dense concentrates, leading to less rumen fermentation and lower degradation rates, and subsequently lower total nutrient intake and calf growth.…”
Section: Forage Factorsmentioning
confidence: 99%
“…For example, cellulolytic microbes, such as Ruminococcus flavefaciens and Ruminococcus albus, are more prevalent in animals fed high forage diets, which increase fiber degradation and elevates the proportion of acetate in the rumen [42,52]. Both propionate and butyrate stimulate and enhance rumen epithelial development [12,13,99], with butyrate serving as the preferred energy source as well as modulating the gene expression in the rumen epithelium [96]. A low proportion of these two VFA may limit the growth of rumen papillae [42,52].…”
Section: Rumen Fluid Ph and Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…From our data, SARA does not appear to negatively affect feed intake and growth performance of calves during the weaning transition. It has previously been suggested that low rumen pH may be advantageous during rumen epithelial development (Stobo et al, 1966), as decreased luminal pH can depress epithelial intracellular pH in vitro (Müller et al, 2000). Modest acidification of intracellular pH to 7.0 prevented cellular apoptosis in kidney cells (Akimova et al, 2006), and activated mitogen-activated protein kinase signaling pathways, leading to cell proliferation (Sarosi et al, 2005).…”
Section: Rumen Ph and Overall Growthmentioning
confidence: 99%